Citizen journalism and their influenceto the collection and content of news (Herald of Journalism, 2022)
This article discusses issues of citizen journalism. Researchers have given many definitions of what citizen journalism is, which is detailed in the first part of this article. The second part examines the advan- tages and disadvantages of the citizen journalism. Also, this article explores the role of citizen journalism in the dissemination of news. With the advent of new technologies, each user can publish any informa- tion, upload photos, video on the internet, which allows them to be a journalist. This trend says that professional journalists have competitors. Can we call them competitors?This article gives an answer to this question considering the advantages and disadvantages, and the possibilities of professional and citi- zen journalism. The topic of this article is relevant in the century of new technologies and innovations.Key words: citizen journalism, traditional journalism, news, content of news, the benefits of citizen journalism, drawbacks of citizen journalism